Correlation between HPV status at T and N sites of oropharyngeal squamous cell carcinomas. (2nd December 2017) - Josiassen, Michael Vallop; Charabi, Birgitte; Lajer, Christel Braemer; Garnaes, Emilie; Hamilton Therkildsen, Marianne; Norrild, Bodil; Specht, Lena; Nielsen, Finn Cilius; von Buchwald, Christian
Abstract: Objectives: Human papilloma virus (HPV) is known to be associated with oropharyngeal squamous cell carcinomas (OPSCC) and may potentially play a vital role in tumor metastasis. The purpose of this study was to correlate HPV status of cervical lymph node metastases with their respective primary OPSCC tumor. Methods: Formalin-fixed, paraffin-embedded (FFPE) tissue samples obtained from 34 patients with cervical lymph node metastases were analyzed with HPV 16 DNA polymerase chain reaction (PCR), p16 immunohistochemistry and HPV typing. The results were correlated with the HPV status and type found in the primary tumors of OPSCC. Results: Comparing HPV DNA status with p16 we found that 21 primary tumors and lymph node metastases were HPV positive (61.8%) and seven primary tumors and lymph node metastases were HPV negative (20.6%). Six patient samples differed when correlating the primary tumor and lymph node metastasis (17.6%). Conclusions: In this study, HPV status in OPSCCs and their cervical lymph node metastases correlated in the vast majority of cases. However, HPV detection methods may have certain limitations resulting in varying degree of non-correlation. This should be taken into account when stratifying treatment in regard to HPV status.